2020
DOI: 10.1002/cam4.3433
|View full text |Cite
|
Sign up to set email alerts
|

Local ablation vs partial nephrectomy in T1N0M0 renal cell carcinoma: An inverse probability of treatment weighting analysis

Abstract: Objective To compare the survival outcomes of local ablation (LA) and partial nephrectomy (PN) for T1N0M0 renal cell carcinoma (RCC). Method We identified 38,155 T1N0M0 RCC patients treated with PN or LA in 2004‐2016 from the retrospective Surveillance, Epidemiology, and End Results databases. Among them, there were 4656 LA and 33,499 PN. A Cox proportional hazards regression model, cause‐specific Cox regression and Fine and Gray sub‐distribution hazard ratio (sHR) with inverse probability of treatment weighti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…After furtherly analyzing our data, we found that about 92% of RCC patients who underwent cryosurgery/radiofrequency surgery were T1a stage, and with a median tumor size of 2.5cm (data not shown). Prior studies indicated that cryosurgery/ radiofrequency surgery in T1a RCC patients showed a comparable survival outcome in comparison with PN (25,26), especially for small tumor size RCC (27). Therefore, it may be linked to the use of these treatments only in low TNM stage tumors, which are associated with a higher risk of SPM.…”
Section: Discussionmentioning
confidence: 99%
“…After furtherly analyzing our data, we found that about 92% of RCC patients who underwent cryosurgery/radiofrequency surgery were T1a stage, and with a median tumor size of 2.5cm (data not shown). Prior studies indicated that cryosurgery/ radiofrequency surgery in T1a RCC patients showed a comparable survival outcome in comparison with PN (25,26), especially for small tumor size RCC (27). Therefore, it may be linked to the use of these treatments only in low TNM stage tumors, which are associated with a higher risk of SPM.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 24 , 25 Current data suggest that thermal ablative therapies may have a similar rate of local recurrence compared to PN in T1aN0M0 tumours, however; this may not be accurate for T1b tumours and there is the risk of selection bias when comparing against patients fit for surgery. 5 , 26 30 Thermal ablative therapies are not suitable for use on centrally located renal tumours, due to the potential risk of damaging the collecting system and the risk of heat sink. 6 , 8 IRE may have a unique role in clinical practice as an alternative to radical nephrectomy for this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…radikalen Nephrektomie nachweisbar. In einer weiteren Auswertung von 38.155 Patienten welche entweder mittels perkutaner Ablation (n = 4656) oder partieller Nephrektomie (n = 33.499) behandelt wurden zeigte sich, das chirurgisch behandelte Patienten zwar insgesamt eine bessere Prognose hatten, das Gesamtüberleben bei älteren Patienten (> 85 Jahre), Patienten mit kleinem NCC (< 2 cm) und Patienten mit chromophobem NCC jedoch vergleichbar war [30].…”
Section: Vergleichende Studienunclassified